A rare case of posterior wall uterovaginal rupture in a primigravida: points to ponder in a peripheral set up - Chourey, Niraj; Hiremath, Ravishekar N.; Chaudhary, Saroj Kumar; Sinha, Pooja; Sandhu, Namratha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Rupture of uterus in a primigravida lady is extremely rare and in most cases it is unalarmed or totally unexpected. The incidence of uterine rupture in general (primigravida or multigravida) is significantly higher in developing countries than in developed countries. Here we present a healthy 24-year-old primigravid woman presented in labor at 39 weeks of gestation with no known comorbidity. She had no significant past medical history and her antenatal care had been uneventful. Intraoperatively the patient was found to have posterior utero-vaginal tear which was repaired subsequently. This case of primigravida, is a rare one and important points to ponder in a periphery setup are discussed here.